Studi Perancangan Sistem Pembumian Gardu Induk 150/20 KV Di Gardu Induk Garuda Sakti - Rahmadhani, Citra; Ervianto, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The earthing system is a system that should be applied in substations. Its function is to protect both humans and equipments are located around the substation of the danger caused by electrical system fault. The fault that often occurs is short circuit to ground which can cause different voltage gradient between points around the substation. The earthing system is expected to overcome the problems occurred, so that in its design should follow applicable standards. The design of the earthing system at 150/20 kV substation refers to the IEEE Std 80-2000. In this paper, earthing system is designed based on the field datas are extracted from substation Garuda Sakti. Based on design verification, its obtained such as following result i.e. mesh voltage 626.38 V, step voltage 344.46 V, length of the conductor grid 2300 m with 0.55 ? resistance and the conductor achieved in this design able to cover area of 86, 59 mm2. Overall of design was complience to the IEEE Std 80-2000.Keywords - earthing system, substation, touch voltage, step voltage